The Synergistic Hepatoprotective Activity of Rosemary Essential Oil and Curcumin: The Role of the MEK/ERK Pathway - Maged E. Mohamed; Nancy S. Younis; Hossam S. El-Beltagi; Omar M. Mohafez (Molecules, 2022)
Background: Curcumin is a natural product obtained from the rhizome of Curcuma longa. Rosemary (Rosmarinus officinalis) is a medicinal and aromatic plant that is widely spread in the Mediterranean region. Both Curcumin and rosemary essential oil are natural products of high medicinal and pharmacological significance. The hepatoprotective effect of both natural products is well-established; however, the mechanism of such action is not fully understood. Thus, this study is an attempt to explore the hepatoprotective mechanism of action of these remedies through their effect on MEK and ERK proteins. Furthermore, the effect of rosemary essential oil on the plasma concentration of curcumin has been scrutinized. Materials and methods: The major constituents of REO were qualitatively and quantitatively determined by GC/MS and GC/FID, respectively. Curcumin and rosemary essential oil were given to mice in a pre-treatment model, followed by induction of liver injury through a high dose of paracetamol. Serum liver enzymes, lipid peroxidation, antioxidant activities, the inflammatory and apoptotic biomarkers, as well as the MEK and ERK portions, were verified. The plasma levels of curcumin were determined in the presence and absence of rosemary essential oil. Results: The major constituents of REO were 1,8-cineole (51.52%), camphor (10.52%), and α-pinene (8.41%). The results revealed a superior hepatoprotective activity of the combination when compared to each natural product alone, as demonstrated by the lowered liver enzymes, lipid peroxidation, mitigated inflammatory and apoptotic biomarkers, and enhanced antioxidant activities. Furthermore, the combination induced the overexpression of MEK and ERK proteins, providing evidence for the involvement of this cascade in the hepatoprotective activity of such natural products. The administration of rosemary essential oil with curcumin enhanced the curcuminoid plasma level. Conclusion: The co-administration of both curcumin and rosemary essential oil together enhanced both their hepatoprotective activity and the level of curcumin in plasma, indicating a synergistic activity between both natural products.